2021
DOI: 10.3897/subtbiol.37.57534
|View full text |Cite
|
Sign up to set email alerts
|

Phlebotomine sand flies (Diptera, Psychodidae) from iron ore caves in the State of Pará, Brazil

Abstract: The present study aimed to evaluate the distribution of sand fly species in iron ore caves in the State of Pará, Brazil and to associate the richness and abundance of these insects with the capacity of leishmaniasis transmission. Entomological captures were carried out in the years 2010, 2013, 2014 and 2015, throughout active samples with brushes, along the entire caves’ extension, in dry and rainy periods. A total of 9,807 sand flies were counted during the 532 samplings events, being 4,340 in the dry period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…This could be due to the mining activities conducted in Delanta district to get Opal using traditional methods. Studies conducted in Brazil indicated as caves were important for the protection, feeding, and breeding of sand flies 39,40 . Another study conducted in Thailand also supported that caves are potential breeding sites for sand flies 41 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This could be due to the mining activities conducted in Delanta district to get Opal using traditional methods. Studies conducted in Brazil indicated as caves were important for the protection, feeding, and breeding of sand flies 39,40 . Another study conducted in Thailand also supported that caves are potential breeding sites for sand flies 41 .…”
Section: Discussionmentioning
confidence: 89%
“…Studies conducted in Brazil indicated as caves were important for the protection, feeding, and breeding of sand flies. 39 , 40 Another study conducted in Thailand also supported that caves are potential breeding sites for sand flies. 41 In addition, rocky territories have been identified as the preferred ecology of the vectors.…”
Section: Discussionmentioning
confidence: 94%
“…To date, the economy of the Serra dos Carajás region has been intensified due to mining operations in its huge deposits of iron ore, influencing directly the local urban development and environmental pressures on land use (Palheta et al 2017). The rock outcrops of this region harbor numerous endemic invertebrates (Chagas-Jr & Bichuette 2018; Brescovit et al 2018; Asenjo et al 2019; Campos-Filho et al 2020; Junta et al 2020; Teodoro et al 2021), including some millipede species such as Glomeridesmus spelaeus Iniesta & Wesener, 2012 (Glomeridesmida Latzel, 1884, Glomeridesmidae Latzel, 1884), Pseudonannolene spelaea Iniesta & Ferreira, 2013 (Spirostreptida Brandt, 1833, Pseudonannolenidae Silvestri, 1895), Parastenonia carajas Bouzan & Iniesta, 2019 (Polydesmida Leach, 1815, Chelodesmidae Cook, 1895), and Stemmiulus brasiliensis Iniesta & Ferreira, 2015 (Stemmiulida Pocock, 1894, Stemmiulidae Pocock, 1894) (Iniesta et al 2012; Iniesta & Ferreira 2013, 2015; Bouzan et al 2019).…”
Section: Introductionmentioning
confidence: 99%